Teachers' Emotional Intelligence and Its Impact on Students' Motivation in Teaching and Learning - Rizki Dhian Nushur; Syahrul Yusuf (ACCENTIA: Journal of English Language and Education, 2021)
The values of emotional intelligence possessed by teachers are one of the factors which may influence teacher performance in education. Good performance of teachers will also have an impact on students, including on students’ motivation. Students’ motivation in the learning process is one of the most important factors that must be fostered and developed because in the end it will affect the achievement of learning outcomes. This study aims to investigate the use of teachers’ emotional intelligence at an Islamic private school in North Aceh, Aceh Province and also how it impacts students’ motivation in the teaching and learning process. The study used qualitative research methods. Data were collected by observation, documentation study, and interview. The population of this study were the teachers and students at an Islamic private school in North Aceh. The results showed that the teachers have tried to understand the situation of students, carry out evaluations, and guide students to be better. The teachers also have more prominent social competences and work together with fellow teachers, administrative staff, and the surrounding community.